Havet som förbinder och skiljer åt: Inramad tystnad i skildringen av andra världskrigets finländska krigsbarn - Österlund, Mia (Tidskrift för litteraturvetenskap, 2016)
United and Divided by the Baltic Sea: Framed Silence in the Depiction of Finnish War Children during the Second World War Set in the 1940s, during the Second World War, Ulf Stark and Stina Wirsén’s picturebook Systern från havet (The Sister from the Sea, 2015) uses the Baltic Sea as a central referent in the story of a Finnish girl evacuee sent off to Sweden. Drawing on Lydia Kokkola’s theory of ”framed silence” in the narration of traumatic war memories for children, this article investigates how the wordless depiction of the Baltic Sea functions as a metonym for a child’s war experience. Wirsén’s reductive visual style makes use of contour, negative space and space in order to frame the silent parts of the narration considered too traumatic to reiterate to a young audience. The concept of ”framed silence” traces absences and reductions in the narration, and seeks to discover the meaning of what is left out or told via metonymy. In this article, I argue that Stark and Wirsén’s picturebook encapsulates an implied story about the most extensive evacuation of children during wartime in European history. The war-child genre is contextualized within the framework of this historical picturebook, but the narrative also alludes to contemporary issues, such as European migration and refugee crises.